Clusters on the road to internationalization – evidence from a CEE economy. Issue 4 (18th July 2016) - Jankowska, Barbara; Główka, Cezary
Abstract : Purpose: This paper aims to respond to the call for empirical research on cluster internationalization to learn more about the mechanism of cluster internationalization and the intensity of this process in a Polish context, which is specific due to Poland. Design/methodology/approach: The authors provide a conceptual model of cluster internationalization and show results of their own primary, empirical and quantitative research on cluster internationalization in Poland. Findings: The study reveals that Polish clusters are at the beginning of the internationalization process, particularly of the outward internationalization. The most popular mode of internationalization is exports. The level of Polish cluster internationalization operations is relatively low. Research limitations/implications: Data were provided by cluster managers, but none of the cluster organizations had a reliable monitoring system for the international involvement of cluster members. These results are merely a snapshot; therefore, a longitudinal study should also be carried out. Social implications: The research demonstrates that cluster companies can take advantage of internationalization operations performed by cluster organizations. The attempts of Polish government should be directed to push the internationalization of micros and small and medium-sized enterprises via cluster initiatives on the one hand and on the other hand to develop some kind of incentives for large companies to participate in cluster organizations as in reality exports are dominated by large firms. Originality/value: The main value added of this paper consists in developing the conceptual model of cluster internationalization and applying the model in empirical research on the internationalization of Polish clusters. The study bridges the theory of firm internationalization, especially the approaches to firm internationalization with the theory of clusters. It offers insight into internationalization of clusters in Poland.